The effect of distraction, response mode and age on peripheral target detection to inform studies of lighting for driving. (November 2021) - Fotios, S; Robbins, CJ; Fox, SR; Cheal, C; Rowe, R
It is expected that the detection of peripheral objects, a key visual task for safe driving, is affected by cognitive distraction, by observer age and by the manner in which action is undertaken following detection. An experiment was conducted to measure these effects, using a fixation cross and peripheral target discs displayed on a screen. The experiment was repeated with young (18–25 years) and old (60+years) age groups, with six distraction tasks, and with simple and choice response modes. The older group was found to respond more slowly than the younger group and detected fewer targets. The results suggest that distraction impairs detection, with the degree of impairment depending on the difficulty of the distraction task. Participants were generally slower at responding with choice response but this did not lead to a greater number of missed targets. Where lighting standards are informed by the ability to detect peripheral hazards, the research should represent older people, choice responses and impaired detection due to distraction.